Terahertz transverse-magnetic-polarized waves localized on layered superconductor defect in photonic crystals - Apostolov, S.S.; Iakushev, D.A.; Makarov, N.M.; Shmat’ko, A.A.; Yampol’ski, i V.A. (Радіофізика та електроніка, 2016)
We theoretically study eigenstates of electromagnetic field inside a one-dimensional photonic crystal containing a defect slab of layered superconductor. Basing on the transfer matrix formalism along with the electrodynamics of Josephson plasma, we obtain the dispersion relations describing the THz electromagnetic modes localized on defect. We consider both symmetric and antisymmetric configuration of defect in photonic crystal. The comparison of the dispersion spectra of the localized states for the layered-superconducting defect and the pure insulating defect reveals the features of the studied system. Теоретически исследованы собственные состояния электромагнитного поля в одномерном фотонном кристалле, содержащем дефектную пластину из слоистого сверхпроводника. Основываясь на методе трансфер-матрицы, с использованием электродинамики джозефсоновской плазмы, получены дисперсионные соотношения, описывающие терагерцевые электромагнитные моды, локализованные на дефекте. Рассмотрены симметричная и антисимметричная конфигурации дефекта в фотонном кристалле. Сравнение дисперсионных спектров локализованных состояний для сверхпроводящего и диэлектрического дефектов позволяет выявить особенности изучаемой системы. Теоретично вивчені власні стани електромагнітного поля в одновимірному фотонному кристалі, що містить дефектну пластину з шаруватого надпровідника. Ґрунтуючись на методі трансфер-матриці, з використанням електродинаміки джозефсонівської плазми, отримані дисперсійні співвідношення, які описують терагерцові електромагнітні моди, що локалізовані на дефекті. Розглядаються симетрична і антисиметричну конфігурації дефекту в фотонному кристалі. Порівняння дисперсійних спектрів локалізованих станів для надпровідного і діелектричного дефектів дозволило виявити особливості системи, що досліджується.